Diethylenetriamine/NONOate-doped alginate hydrogel with sustained nitric oxide release and minimal toxicity to accelerate healing of MRSA-infected wounds. (15th October 2021) - Hasan, Nurhasni; Lee, Juho; Kwak, Dongmin; Kim, Hyunwoo; Saparbayeva, Aruzhan; Ahn, Hye-Jin; Yoon, In-Soo; Kim, Min-Soo; Jung, Yunjin; Yoo, Jin-Wook
Abstract : Abstract This study demonstrates the development of a nitric oxide (NO)-releasing hydrogel wound dressing and its efficacy at accelerating methicillin-resistant Staphylococcus aureus (MRSA)-infected wound healing. A DETA/NONOate-doped alginate (Alg-DETA/NO) hydrogel was synthesized using alginate as a hydrogel-forming wound dressing material and diethylenetriamine/diazeniumdiolate (DETA/NONOate) as an NO donor. Alg-DETA/NO exhibited a prolonged NO release profile over a period of 4 days. The rheological properties of Alg-DETA/NO did not differ significantly from those of pure alginate. Importantly, Alg-DETA/NO showed potent antibacterial activity against MRSA, with minimal toxicity to mouse fibroblasts. The application of Alg-DETA/NO to MRSA-infected wounds in a mouse model showed a favorable wound healing with accelerated wound-size reduction and reduced skin bacterial infection. Additionally, histological examination revealed that Alg-DETA/NO reduced inflammation at the wound site and promoted re-epithelialization, angiogenesis, and collagen deposition. Thus, Alg-DETA/NO presented herein could serve as a safe and potent hydrogel dressing for the treatment of MRSA-infected wounds. Graphical abstract: Unlabelled Image Highlights: We synthesized an alginate-diethylenetriamine/NONOate hydrogel (Alg-DETA/NO). Alg-DETA/NO showed NO-releasing properties with low toxicity toward fibroblasts. Alg-DETA/NO absorbed the wound exudate and transformed into a hydrogel. Alg-DETA/NO had excellent therapeutic activities in mice with MRSA-infected wounds. Alg-DETA/NO accelerated wound healing by targeting different wound-healing phases.